Cover Feature: Thiadiazolo‐Azaacenes (Chem. Eur. J. 24/2019). Issue 24 (26th March 2019) - Müller, Matthias; Koser, Silke; Tverskoy, Olena; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract : Fusion of (thiadiazolo)‐butterfly‐type wings onto di‐ and tetraazaacenes, displaying up to seven catenated arene rings, furnishes acenes resistant towards oxidation and dimerization. These derivatives do not show enhanced electron affinities due to the benzothiadiazole units being resonance‐separated from the acene body, maximizing the number of Clar‐sextet analogues. More information can be found in the Communication by U. H. F. Bunz et al. onpage 6082 .